Synthesis of cubic and monoclinic hafnia nanoparticles by pulsed plasma in liquid method. Issue 24 (15th December 2021) - Ma, Weijian; Mashimo, Tsutomu; Tokuda, Makoto; Tamura, Shota; Yoda, Shinichi; Tsushida, Masayuki; Isobe, Hiroshi; Yoshiasa, Akira
Abstract: Hafnia (HfO2, hafnium dioxide) is a wide band gap and high- κ material, and the metastable cubic hafnia has a much higher permittivity compared with the normal monoclinic hafnia. Here, we employ a one-step process, the pulsed plasma in liquid (PPL) method to synthesize two types of hafnia nanoparticles (NPs): one which is mainly in cubic phase (cubic: 81.7 at%, monoclinic: 18.3 at%) and the other which is in monoclinic phase. High-resolution transmission electron microscopy images showed that the particles were small (particle size 3 nm). X-ray absorption fine structure analysis showed no chemical shifts, indicating that the synthetic hafnia NPs contained no oxygen vacancy. The synthetic hafnia NPs mainly in cubic phase showed a much higher relative permittivity than that of the commercial hafnia (monoclinic), and have a larger band gap than the synthetic monoclinic hafnia NPs.